Enteroviral infections are not associated with type 2 diabetes - Liu, Huan; Geravandi, Shirin; Grasso, Ausilia Maria; Sikdar, Saheri; Pugliese, Alberto; Maedler, Kathrin (Frontiers in Endocrinology, 2023)
For more than a century, enteroviral infections have been associated with autoimmunity and Type 1 Diabetes (T1D). Uncontrolled viral response pathways repeatedly presented during childhood highly correlate with autoimmunity and T1D. Virus responses evoke chemokines and cytokines, the “cytokine storm” circulating through the body and attack cells especially vulnerable to inflammatory destruction. Intra-islet inflammation is a major trigger of -cell failure in both T1D and T2D. The genetic contribution of islet inflammation pathways is apparent in T1D, with several mutations in the interferon system. In contrast, in T2D, gene mutations are related to glucose homeostasis in -cells and insulin target tissue and rarely within viral response pathways. Therefore, the current study evaluated whether enteroviral RNA can be found in the pancreas from organ donors with T2D and its association with disease progression. Pancreases from well-characterized 29 organ donors with T2D and 16 age- and BMI matched controls were obtained from the network for Pancreatic Organ Donors with diabetes (nPOD) and were analysed in duplicates. Single molecule FISH analyses were performed using three probe sets to detect positive strand enteroviral RNA; pancreas sections were co-stained by classical immunostaining for insulin and CD45. There was no difference in the presence or localization of enteroviral RNA in control nondiabetic and T2D pancreases; viral infiltration showed large heterogeneity in both groups ranging from 0-94 virus+ cells scattered throughout the pancreas, most of them in the exocrine pancreas. Very rarely, a single virus+ cell was found within islets or co-stained with CD45+ immune cells. Only one single T2D donor presented an exceptionally high number of viruses, similarly as seen previously in T1D, which correlated with a highly reduced number of -cells. No association of enteroviral infection in the pancreas and T2D diabetes could be found. Despite great similarities in inflammatory markers in islets in T1D and T2D, long-term enteroviral infiltration is a distinct pathological feature of T1D-associated autoimmunity and in T1D pancreases.